2019
DOI: 10.1161/hypertensionaha.118.11994
|View full text |Cite
|
Sign up to set email alerts
|

Parental Dietary Protein Source and the Role of CMKLR1 in Determining the Severity of Dahl Salt-Sensitive Hypertension

Abstract: Studies from our laboratory have revealed an important role for the maternal diet as well as the dietary protein source in the development of hypertension and renal injury in Dahl Salt-Sensitive (SS) rats. The current study sought to compare salt-induced hypertension, renal damage, and immune cell infiltration in the offspring of breeders fed either a casein-or gluten-based diet, with the hypothesis that offspring from gluten-fed breeders would fail to develop these salt-sensitive phenotypes. When fed identica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 54 publications
(63 reference statements)
1
21
0
Order By: Relevance
“…Antagonism of Chemerin1 attenuated the hypertension of the Dahl S rat fed high salt, as well as renal damage. 115 These studies are significant in that they support the activation of a chemerin receptor as mediating the disease.…”
Section: Chemerin Measures In Normal and Humans With Cardiovascular Dmentioning
confidence: 96%
See 1 more Smart Citation
“…Antagonism of Chemerin1 attenuated the hypertension of the Dahl S rat fed high salt, as well as renal damage. 115 These studies are significant in that they support the activation of a chemerin receptor as mediating the disease.…”
Section: Chemerin Measures In Normal and Humans With Cardiovascular Dmentioning
confidence: 96%
“… 114 In another study, renal chemerin was elevated in a diabetic model, 31 and Chemerin1 was upregulated in renal T cells in casein fed progeny of the Dahl S rat. 115 This latter study used 2-(α-naphthoyl)ethyltrimethylammonium iodide as a Chemerin1 antagonist. Antagonism of Chemerin1 attenuated the hypertension of the Dahl S rat fed high salt, as well as renal damage.…”
Section: Chemerin Measures In Normal and Humans With Cardiovascular Dmentioning
confidence: 99%
“…A, PCoA plot of the weighted UniFrac distance matrix demonstrating that FMT from SS/MCW donors significantly shifted the gut microbial community of SS/CRL recipients (PERMANOVA (all) P = .001; Pairwise PERMANOVA: Donor vs FMT P = .006, Donor vs Vehicle P = .004, Vehicle vs FMT P = .029). B, Global differences in relative abundance of identified ASVs in FMT and vehicle-treated rats at Weeks at Weeks 5, 15 While the SS/CRL Vehicle rats could certainly be described as hypertensive, it is important to note that the disease resistant nature of the SS/CRL is what has allowed these rats to survive a 12 week-long high salt challenge. Additionally, there were no significant changes in heart rate between the two groups (375.0 ± 3.4 vs 362.4 ± 10.1 bpm, FMT vs Vehicle, P = .31, data not shown).…”
Section: Ss/mcw Gut Microbiota Into Protected Ss/ Crl Recipient Rats Raises Blood Pressure Increases Renal Damage and Increases Renal T Cmentioning
confidence: 99%
“…[12][13][14][15] More specifically, this effect of the purified vs grain diet has been attributed to the difference in dietary protein source (casein vs wheat gluten), 12 where there is a clear contribution of the adaptive immune system. [13][14][15] Our recent efforts to understand the influence of the non-sodium components of the diet on salt-sensitive hypertension and renal damage have demonstrated that these changes are related to substantial differences in DNA methylation 16 and gene expression 11 in T-lymphocytes which alter the inflammatory phenotype and ultimately disease severity. As a result of the significant immune-mediated dietary effects observed in the Dahl SS rat and the increasing evidence for the role of the gut microbiota in hypertension and immunity, we hypothesized that the gut microbiota compositions of SS/MCW and SS/CRL are driven by these dietary alterations.…”
Section: Introductionmentioning
confidence: 99%
“…Renal immune cells. Immune cells in the kidney were isolated as previously described (1,2). Briefly, the left kidney was minced and incubated in RPMI-1640 media containing L-glutamine, HEPES, collagenase type IV, and DNase.…”
Section: Immune Cell Isolationmentioning
confidence: 99%